Recent Advances in Drug Delivery Approaches for Rheumatoid Arthritis - Verma, Abhishek; Patel, Preeti; Almalki, Waleed Hassan; Sahebkar, Amirhossein; Das Kurmi, Balak; Kesharwani, Prashant (Current Medicinal Chemistry, 2025)
Morbidity, disability, and healthcare expenses associated with rheumatoid arthritis (RA) impose a considerable health and economical burden on both patients and healthcare systems. This review aimed to examine the pathophysiological aspects of RA that may help design different types of drugs and drug delivery systems. These include monoclonal antibodies, immunoglobulins, tiny chemicals, and transgenes for gene therapy. These novel nanocarrier-based therapies target the underlying biological processes involved in RA while minimizing the systemic adverse effects of drugs.
Keywords: Rheumatoid arthritis